PENGARUH STIMULUS PEMASARAN DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PERUMAHAN CITRA GARDEN DI KOTA PEKANBARU - Bayu Rosyahdi; Jushermi Jushermi; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analysze Marketing Stimuli and Coorporation Image to Purcashing Decision and Customer Satisfaction on Citra Garden Residential in Pekanbaru. There are four variables in this research such as Marketing Stimuli (X1), Coorporation Image (X2), Purcashing Decision (Y1), and Customer Satisfaction (Y2). The population in this research amounted 95 people, while the sampling technique was done by census method. This research use Path Analysis method by SPSS version 20. The result of this research shows that Marketing Stimuli have significant effect to Purcashing Decision and Marketing Stimuli have positive and significant effect to Customer Satisfaction. Coorporation Image have significant effect to Purcashing Decision and Coorporation Image have positive and significant effect to Customer Satisfaction. Purchasing Decision have significant effect to Customer Decision. The last is, the path of Marketing Stimuli and Coorporation Image have strong effect to Consumer Satisfaction with Purchasing Decision as intervening variable.Keywords: Marketing Stimuli, Coorporation Image, Purcashing Decision, Costumer Satisfaction